Production Leveling System Implementation at Mixed Model Product with Heterogeneous Cycle Time for Single Operation Line - Adnan, Ahmad Naufal; Ismail, A. (International Journal of Integrated Engineering, 2020)
Production leveling is one of the main lean manufacturing principles which aims to enhance production performance and optimize operation cost. Systematic and level production of process for mixed model product is presented to study manufacturing parameter results. A required production time was synched in leveling system approach to avoid non-value-added item such as excess inventory and poor planning in production space. A few parameters were used to measure the performance of production leveling system implementation. Proper establishment production leveling schedule gained good results for manufacturers who were committed to the implementation. The most significant production area and productivity were due to balanced capacity according to actual demand. The conclusion and recommendation regarding potentials of efficient implementation were presented in a demonstration of production leveling system at mixed model product at single operation line.